2014
DOI: 10.1002/ejp.522
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence and its determinants after spinal cord injury: A systematic review

Abstract: Pain prevalence studies are important as they illustrate the magnitude of pain problems in a certain patient population, such as patients living with a spinal cord injury (SCI). Strikingly, reported pain prevalence rates in SCI patients are found to vary greatly, while determinants for the differences between pain prevalence reports remain unclear. We here aim to identify determinants for the differences (heterogeneity) in pain prevalence reports through a systematic review of all SCI pain prevalence reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 65 publications
2
73
1
1
Order By: Relevance
“…Sensory dysfunction is of major clinical relevance, as the majority of SCI patients report some pain [15] and NP occurs in over 50% of patients with a SCI [1618]. Understanding how outcome measures of sensory plasticity change during recovery is essential for cross-species translation, especially when translating novel treatments emerging from preclinical research into the clinical setting [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sensory dysfunction is of major clinical relevance, as the majority of SCI patients report some pain [15] and NP occurs in over 50% of patients with a SCI [1618]. Understanding how outcome measures of sensory plasticity change during recovery is essential for cross-species translation, especially when translating novel treatments emerging from preclinical research into the clinical setting [19].…”
Section: Introductionmentioning
confidence: 99%
“…musculoskeletal, visceral) pain of varying intensity, quality and constancy. [1][2][3] For many, this results in a pain continuum, from acute biomedical treatment through to management of persistent pain. 4,5 SCI pain management is further complicated by a multitude of cognitive, emotional, behavioural and social factors that can adversely affect, or buffer, the pain experience.…”
Section: Introductionmentioning
confidence: 99%
“…49 Did the other 10 studies also include individuals with pain? Considering that pain is reported to affect one half to two thirds of persons with SCI, 1 it is very likely that these studies included individuals with one or more types of pain. Indeed, 2 studies hinted toward the inclusion of individuals with pain by reporting gabapentin use (a drug prescribed for neuropathic pain management) 56 or having lost a patient at follow-up due to increased knee and low back pain.…”
Section: The Problemmentioning
confidence: 99%